1957
DOI: 10.1111/j.1476-5381.1957.tb00143.x
|View full text |Cite
|
Sign up to set email alerts
|

THE ACTION OF SUBSTANCES ANALOGOUS TO DIAMINODIPHENOXYALKANES AGAINST SCHISTOSOMA MANSONI

Abstract: The effects on activity against Schistosoma mansoni of further modifications of the diaminodiphenoxyalkanes are reported. Replacement of the amino‐group by any of a large number of other groups destroys activity. Activity is retained in the presence of certain substituted (hydroxyalkyl, carboxyalkyl) amino‐groups and in some of their aldehyde‐bisulphite derivatives. Many variations of the central chain lead to compounds of reduced activity, the outstanding exceptions being a number of but‐2‐ene derivatives, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1958
1958
1973
1973

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…This field was covered thoroughly by Raison and Standen (1955) and Gorvin et al (1957). Our results agree very well with theirs with the single exception of the isopropyl derivative, which Raison and Standen (1955) found to be active.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…This field was covered thoroughly by Raison and Standen (1955) and Gorvin et al (1957). Our results agree very well with theirs with the single exception of the isopropyl derivative, which Raison and Standen (1955) found to be active.…”
supporting
confidence: 80%
“…Branched chains (Table II) had a deleterious effect, as Gorvin et al (1957) also found, but compounds with a double bond in the chain were as active as those with a saturated chain. It is doubtful if the apparent difference in activity between the cis and trans isomers was significant.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Effect of N-substitution (Table 9) The results given here demonstrate that N-substituted compounds were active although they were sometimes less so than the corresponding primary amines, as found by Raison & Standen (1955); Gorvin, Raison, Solomon, Standen & Walls (1957) and Collins et al (1958Collins et al ( , 1959.…”
Section: Resultsmentioning
confidence: 92%